Branched-chain amino acids are associated with metabolic parameters in bipolar disorder. (26th November 2019) - Fellendorf, Frederike T.; Platzer, Martina; Pilz, Rene; Rieger, Alexandra; Kapfhammer, Hans-Peter; Mangge, Harald; Dalkner, Nina; Zelzer, Sieglinde; Meinitzer, Andreas; Birner, Armin; Bengesser, Susanne A.; Queissner, Robert; et al.
Abstract: Objectives: An important aspect of bipolar disorder (BD) research is the identification of biomarkers pertaining to the somatic health state. The branched-chain essential amino acids (BCAAs), viz valine, leucine and isoleucine, have been proposed as biomarkers of an individual's health state, given their influence on protein synthesis and gluconeogenesis inhibition. Methods: BCAA levels of 141 euthymic/subsyndromal individuals with BD and 141 matched healthy controls (HC) were analysed by high-pressure lipid chromatography and correlated with clinical psychiatric, anthropometric and metabolic parameters. Results: BD and HC did not differ in valine and isoleucine, whereas leucine was significantly lower in BD. Furthermore, correlations were found between BCAAs and anthropometric and glucose metabolism data. All BCAAs correlated with lipid metabolism parameters in females. There were no associations between BCAAs and long-term clinical parameters of BD. A negative correlation was found between valine and Hamilton Depression-Scale, and Beck Depression Inventory II, in male individuals Conclusions: Our results indicate the utility of BCAAs as biomarkers for the current state of health, also in BD. As BD individuals have a high risk for overweight/obesity, in association with comorbid medical conditions (e.g. cardiovascular diseases or insulin resistance), health state markers are urgently required. However, no illness-specific associations were found in this euthymic/subsyndromal BD group.